Pengaruh Media Scrapbook Terhadap Hasil Belajar Keterampilan Berbicara Siswa Kelas Iv Di Upt Sdn Tabang No. 24 Kepulauan Selayar - Widya Ayuning; Muhammad Akhir; Abdan Syakur (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This research aims to determine the effect of using Scrapbook media on the speaking skills learning outcomes of Class IV UPT SDN Tabang No. Students. 24 Selayar Islands. This research is experimental research, namely the Pre-Experimental Design type. The population and sample in this study were all class IV students at UPT SDN Tabang No. 24 Selayar Islands, totaling 20 people. This research was carried out at UPT SDN Tabang No. 24 Selayar Islands. Based on the results of student activity before using Scrapbook media during the pretest, it shows that student activity is still not active, where the average score of student activity in learning is 5.68% and after applying Scrapbook media during the posttest shows a significant change in student activity, where the score The average student activity in learning is 95%. The results of data analysis, student learning outcomes after applying Scrapbook media to students' speaking skills showed that the average score of students experienced a significant change, namely 94.3 higher with a score range of 41 compared to the pretest or before the treatment was implemented, namely 47.16 with a score range 69. Based on the test results, it can be concluded that the use of Scrapbook media influences the speaking skills learning outcomes of class IV UPT SDN Tabang No. students. 24 Selayar Islands.